Preferensi tamu terhadap pelayanan Room Attendant di Doubletree by Hilton Johor Bahru pada masa pandemic covid -19 - Ni Luh Somawati; Ni Nyoman Suci Arthini; I Made Sucipta Adnyana; Ni Ketut Iswarini (Program Studi Manajemen Divisi Kamar, 2022)
Guest preferences for room attendant services at Doubletree by Hilton Johor Bahru during the COVID-19 pandemic need to be detailed because of guest complaints that have been submitted via OTA. This complaint will have an impact on the hotel's image. This study aims to provide ideas and insights for decision makers in order to improve Room Attendant by understanding the preferences of guests staying at Doubletree Hotel.The type of data used by the writer is qualitative descriptive data and data collection techniques used ware documentation study and interviews. Data analysis techniques used to describe guest preference lists and guest reviews on the OTA for room attendant services with reference to hospitality, attraction, cleanliness, comfort, and safety at this hotel. Then analyzes preferences in the form of the most preffered reviews and the least preffered preference. In the research, it can be concluded that the reviews that appear the most are guests who like the room to be cleaned at breakfast, expect extra water and towels and the least preferred appears: does not like strong smells, guests prefer turn down service when guests are outside the room, and don't like the consistency of housekeeping and don't like the worn bed sheets.